Prevalence of Nomophobia and Its Impact on Academic Performance Among Respiratory Therapy Students in Saudi Arabia - Aldhahir AM; Bintalib HM; Siraj RA; Alqahtani JS; Alqarni OA; Alqarni AA; Alghamdi HS; Alyami MM; Naser AY; Fatani AI; Alwafi H (Psychology Research and Behavior Management, 2023)
Abdulelah M Aldhahir,1 Heba M Bintalib,2,3 Rayan A Siraj,4 Jaber S Alqahtani,5 Omar A Alqarni,6 Abdullah A Alqarni,7 Hanin S Alghamdi,8 Mohammed M Alyami,9 Abdallah Y Naser,10 Alaa I Fatani,11 Hassan Alwafi11 1Respiratory Therapy Department, Faculty of Applied Medical Sciences, Jazan University, Jazan, Saudi Arabia; 2Department of Respiratory Care, King Saud bin Abdulaziz University for Health Sciences, Jeddah, Saudi Arabia; 3King Abdullah International Medical Research Centre, Jeddah, Saudi Arabia; 4Department of Respiratory Care, College of Applied Medical Sciences, King Faisal University, Al-Ahsa, Saudi Arabia; 5Department of Respiratory Care, Prince Sultan Military College of Health Sciences, Dammam, Saudi Arabia; 6Clinical Technology Department, Respiratory Care Program, Faculty of Applied Medical Sciences, Umm Al-Qura University, Makkah, Saudi Arabia; 7Department of Respiratory Therapy, Faculty of Medical Rehabilitation Sciences, King Abdulaziz University, Jeddah, Saudi Arabia; 8Department of Respiratory Therapy, King Fahad General Hospital, Jeddah, Saudi Arabia; 9Respiratory Therapy Department, Batterjee Medical College, Khamis Mushait, Saudi Arabia; 10Department of Applied Pharmaceutical Sciences and Clinical Pharmacy, Faculty of Pharmacy, Isra University, Amman, Jordan; 11Faculty of Medicine, Umm Al-Qura University, Mecca, Saudi ArabiaCorrespondence: Abdulelah M Aldhahir, Respiratory Therapy Department, Faculty of Applied Medical Sciences, Jazan University, Saudi Arabia, Tel +966557775561, Email Aldhahir.abdulelah@hotmail.comBackground: Nomophobia has been highly prevalent among health discipline students. However, there is no available data on the prevalence of nomophobia among respiratory therapy (RT) students in Saudi Arabia.Methods: A cross-sectional survey using the nomophobia questionnaire (NMP-Q) was conducted and distributed using a convenience sample of RT students through an online platform (Survey Monkey) between September and November 2022.Results: Overall, 1428 RT students, with males accounting for 773 (54%), responded to the online survey. The prevalence of nomophobia among RT students was 97.3% (1390). The mean (±SD) of the total NMP-Q items scores was 62 (± 22), indicating a moderate level of nomophobia among the RT students. Female RT students had significantly higher nomophobia scores than male RT students (63 (47– 80) vs 59 (43– 75); p < 0.001)). Single RT students had significantly higher nomophobia scores than married RT students (62 (46– 78) vs 46 (37– 64); p < 0.001)). RT students who were living outside the family home had significantly higher nomophobia scores than RT students who were living with their family (66 (54– 78) vs 60 (44– 77); p = 0.001)). RT students with a GPA of 4.50 to 5.00 had the highest nomophobia score (63 (46– 79); p = 0.005)). RT students who were in their third year had the highest nomophobia score (66 (48– 80); p < 0.001)). RT students who reported no academic warnings had the highest nomophobia score (63 (48– 80); p < 0.001)). RT students who spent ≥ five hours studying per week had the highest nomophobia score (64 (51– 80); p < 0.001)).Conclusion: Nomophobia is common among RT students, with the majority experiencing a moderate level. Being female, single, living outside the family home, and having a higher academic performance were risk factors associated with higher nomophobia levels.Keywords: nomophobia, respiratory therapy, NMP-Q